Inhibition of macrophage infectivity potentiator in Burkholderia pseudomallei suppresses pro-inflammatory responses in murine macrophages - Iwasaki, Jua; Bzdyl, Nicole M.; Lin-Sullivan, Dion J. M.; Scheuplein, Nicolas J.; Dueñas, Maria Emilia; de Jong, Emma; Harmer, Nicholas J.; Holzgrabe, Ulrike; Sarkar-Tyson, Mitali (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Melioidosis, caused by the Gram-negative bacterium Burkholderia pseudomallei, is a disease endemic in many tropical countries globally. Clinical presentation is highly variable, ranging from asymptomatic to fatal septicemia, and thus the outcome of infection can depend on the host immune responses. The aims of this study were to firstly, characterize the macrophage immune response to B. pseudomallei and secondly, to determine whether the immune response was modified in the presence of novel inhibitors targeting the virulence factor, the macrophage infectivity potentiator (Mip) protein. We hypothesized that inhibition of Mip in B. pseudomallei would disarm the bacteria and result in a host beneficial immune response. Methods Murine macrophage J774A.1 cells were infected with B. pseudomallei K96243 in the presence of small-molecule inhibitors targeting the Mip protein. RNA-sequencing was performed on infected cells four hours post-infection. Secreted cytokines and lactose dehydrogenase were measured in cell culture supernatants 24 hours post-infection. Viable, intracellular B. pseudomallei in macrophages were also enumerated 24 hours post-infection. Results Global transcriptional profiling of macrophages infected with B. pseudomallei by RNA-seq demonstrated upregulation of immune-associated genes, in particular a significant enrichment of genes in the TNF signaling pathway. Treatment of B. pseudomallei-infected macrophages with the Mip inhibitor, AN_CH_37 resulted in a 5.3-fold reduction of il1b when compared to cells treated with DMSO, which the inhibitors were solubilized in. A statistically significant reduction in IL-1β levels in culture supernatants was seen 24 hours post-infection with AN_CH_37, as well as other pro-inflammatory cytokines, namely IL-6 and TNF-α. Treatment with AN_CH_37 also reduced the survival of B. pseudomallei in macrophages after 24 hours which was accompanied by a significant reduction in B. pseudomallei-induced cytotoxicity as determined by lactate dehydrogenase release. Discussion These data highlight the potential to utilize Mip inhibitors in reducing potentially harmful pro-inflammatory responses resulting from B. pseudomallei infection in macrophages. This could be of significance since overstimulation of pro-inflammatory responses can result in immunopathology, tissue damage and septic shock.